Pengaruh Literasi Keuangan, Perilaku Pembelian Impulsif, dan Gaya Hidup Terhadap Penggunaan Shopee Paylater pada Mahasiswa Universitas Bengkulu (Gen Z) - Mey Zara; Tiara Pracilia Hanipah; Aura Tryana Gustitantira; Seli Pia Junita; Anggi Noverita; Cantika Alifa Irawan (Indo Publishing, 2026)
The use of PayLater as a payment method can influence people’s lifestyles, particularly among Generation Z (1997–2012), who are familiar with technology. Although most of them do not yet have an income, Gen Z shows a high tendency to shop using PayLater, but often faces difficulties in managing their bills. Previous studies have examined the influence of financial literacy, impulsive behavior, and lifestyle on PayLater usage; however, they have not discussed its impact on hedonistic lifestyles that do not align with budgets. The advancement of financial technology, ease of access, fast registration processes, and various e-commerce promotions have further increased the use of PayLater among students. Therefore, this study aims to re-examine the influence of financial literacy, impulsive behavior, and lifestyle on PayLater usage among Gen Z at the University of Bengkulu, involving 100 respondents, It was found that financial literacy has a negative effect, while impulsive buying behavior and lifestyle have a positive effect on the use of Shopee PayLater among Generation Z at the University of Bengkulu.